Ni-WC Coating on AISI 1010 Steel Using TIG: Microstructure and Microhardness - Tosun, Gul (Springer Heidelberg, 2014)
In this study, mixed powders of Ni and WC were coated using tungsten inert gas method on the surface of AISI 1010 steel. The effects of current and thickness of the preplaced powder layer on the microstructure and hardness of the alloyed surfaces were investigated. The hardness of the alloyed surfaces increased and this was attributed to harder phases. Different microstructures were observed depending on the production parameters. The microstructures of the alloyed surfaces consisted of widmanstatten-type ferrite, grain boundary ferrite, acicular ferrite, bainite and a small amount of martensite phase.
Keywords: Ni-WC; Coating; Hardness; Microstructure